Lead-free piezoelectric (Ba,Ca)(Ti,Zr)O3 scaffolds for enhanced antibacterial property - Sugimoto, Hina; Biggemann, Jonas; Fey, Tobias; Singh, Priya; Khare, Deepak; Dubey, Ashutosh Kumar; Kakimoto, Ken ichi (Materials Letters, 2021)
Scaffolds with particularly high antimicrobial properties based on (Ba, Ca)(Ti, Zr)O3 (BCTZ), a lead-free piezoelectric material, was fabricated using the polyurethane foam template replica method. The surface of the scaffolds was successfully coated with 13–93 bioactive glass (BG) using dip coating method. The developed scaffolds were polarized using corona poling unit. The charged surfaces of BCTZ scaffolds revealed good antibacterial response. After polarization, 13–93 BG coated BCTZ scaffold recorded 42%–49% reduction in the survival rate of Escherichia coli bacteria relative to the standard sample. Overall, such an approach can be suggested to improve the biocompatibility due to bioactive glass, prevent leaching of ions from BCTZ and provide a reasonably good antibacterial characteristic to the developed scaffolds.
CRIS-Team Scopus Importer:2021-05-21
Keywords: (Ba; Ca)(Ti; Zr)O; Antibacterial property; Lead-free piezoelectrics; Porous scaffold